2020
DOI: 10.3390/ma13061373
|View full text |Cite
|
Sign up to set email alerts
|

Citrate and Polyvinylpyrrolidone Stabilized Silver Nanoparticles as Selective Colorimetric Sensor for Aluminum (III) Ions in Real Water Samples

Abstract: The use of silver nanoparticles stabilized with citrate and polyvinylpyrrolidone as a sensor for aluminum ions determination is proposed in this paper. These non-functionalized and specific nanoparticles provide a highly selective and sensitive detection system for aluminum in acidic solutions. The synthesized nanoparticles were characterized by transmission electron microscopy. Surface plasmon band deconvolution analysis was applied to study the interaction between silver nanoparticles and aluminum ions in so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 43 publications
(75 reference statements)
0
1
0
Order By: Relevance
“…The advantages of PVP over the SDS capping agent; 1—the former leads to the synthesis of more uniform particle size, 2—PVP-capped AgNPs have superior antibacterial and anti-fungal activities; which prolongs their shelf-life [ 46 ], 3—PVP-capping helps to stabilize the AgNPs by forming steric protective shields, allowing steric and electrostatic stabilization [ 17 ], and finally 4—PVP-capping provides excellent physicochemical properties like solubility in both water and organic solvents, biocompatibility, and non-toxicity [ 47 ]. Comparing the PVP-capped AgNPs to citrate-capped AgNPs; PVP-capped was found to be more stable [ 48 ] and had smaller particle size which improved the method sensitivity [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…The advantages of PVP over the SDS capping agent; 1—the former leads to the synthesis of more uniform particle size, 2—PVP-capped AgNPs have superior antibacterial and anti-fungal activities; which prolongs their shelf-life [ 46 ], 3—PVP-capping helps to stabilize the AgNPs by forming steric protective shields, allowing steric and electrostatic stabilization [ 17 ], and finally 4—PVP-capping provides excellent physicochemical properties like solubility in both water and organic solvents, biocompatibility, and non-toxicity [ 47 ]. Comparing the PVP-capped AgNPs to citrate-capped AgNPs; PVP-capped was found to be more stable [ 48 ] and had smaller particle size which improved the method sensitivity [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, the clear colorless solution gives a bright yellow color indicating the fabrication of AgNPs. After that, the colored solution was further stirred at zero temperature for 2 h, kept in a brown bottle, and stored at 4 °C [ 39 , 40 ]. The obtained AgNPs were denoted PVA-Cit-AgNPs.…”
Section: Methodsmentioning
confidence: 99%
“…The methods, where the AgNO3 was reduced using the fabricated fibers after the electrospinning process, presented a small or less evident presence of the AgNPs over the fibers compared to those samples, where the AgNO3 was reduced using the PCL-PVP polymeric solution before the electrospinning process, which presented a more abundant, higher distribution and bigger AgNPs sizes. These differences can be observed because of the role of PVP in the AgNO3, because it has been reported in the literature that PVP works as a stabilizer in the AgNPs formation producing nanoparticles with smaller sizes [36,37]. Zein, et al [36], concluded that adding PVP as a stabilizing agent during the synthesis process decreases the size of AgNPs and yields more stable colloidal AgNPs than uncoated nanoparticles.…”
Section: Scanning Electron Microscopymentioning
confidence: 99%